DISCOURSE CONNECTORS IN THE ESP STUDENTS’ WRITINGS: A PRELIMINARY STUDY - Wuwuh Andayani (Universitas PGRI Palembang, 2024)
Cohesion and coherent writing are important aspects of a well-written paragraph. For a paragraph to successfully communicate its meaning, it must be coherent and cohesive. Examining how English for Specific Purposes (ESP) students use discourse connectors in their writing was the aim of this study. The argumentative essays written by students enrolled in English for Specific Purposes (ESP) courses were the main focus of the study. Thirty-six essays from ESP students were chosen as the sample for this study using a purposive sampling technique. Methods of quantitative analysis were applied to the data. The results showed that the students' use of a wide variety of discourse connectors was lacking. Furthermore, they did not use enough accurate discourse connections. Additionally, it was seen that discourse connectors were being used excessively. In addition, the discourse connectors